Disruptive impacts of automated driving systems on the built environment and land use: An urban planner's perspective - Tan Yigitcanlar; Mark Wilson; Md Kamruzzaman (Journal of Open Innovation: Technology, Market, and Complexity, 2019)
Cities have started to restructure themselves into 'smart cities' to address the challenges of the 21st Century-such as climate change, sustainable development, and digital disruption. One of the major obstacles to success for a smart city is to tackle the mobility and accessibility issues via 'smart mobility' solutions. At the verge of the age of smart urbanism, autonomous vehicle technology is seen as an opportunity to realize the smart mobility vision of cities. However, this innovative technological advancement is also speculated to bring a major disruption in urban transport, land use, employment, parking, car ownership, infrastructure design, capital investment decisions, sustainability, mobility, and traffic safety. Despite the potential threats, urban planners and managers are not yet prepared to develop autonomous vehicle strategies for cities to deal with these threats. This is mainly due to a lack of knowledge on the social implications of autonomous capabilities and how exactly they will disrupt our cities. This viewpoint provides a snapshot of the current status of vehicle automation, the direction in which the field is moving forward, the potential impacts of systematic adoption of autonomous vehicles, and how urban planners can mitigate the built environment and land use disruption of autonomous vehicles.
Keywords: 650; autonomous vehicle; autonomous driving; disruptive technology; land use change; built environment; smart city; smart urbanism; smart mobility; urban innovation; urban planning